Properties of Inclined Silicon Carbide Thin Films Deposited By Vacuum Thermal Evaporation - Khalid Z. Yahiya; Ammar H. Jraiz; Najem Abdu Al-Kazem (Engineering and Technology Journal, 2008)
In this work, thermal evaporation system was employed to deposit thin films of SiC onglass substrates in order to determine the parameters of them. Measurements includedtransmission, absorption, Seebak effect, resistivity and conductivity, absorption coefficient,type of energy band-gap, extinction coefficient as functions of photon energy and the effectof increasing film thickness on transmittance. Results explained that SiC thin film is an ntypesemiconductor of indirect energy and-gap of ~3eV,cut-off wavelength of 448 nm,absorption coefficient of 3.4395x104cm-1 and extinction coefficient of 0.154. Theexperimental measured values are in good agreement with the typical values of SiC thinfilms prepared by other advanced deposition techniques.